Cluster training: A novel method for introducing training program variation - Haff, G. G.; Hobbs, R. T.; Haff, E. E.; Sands, W. A.; Pierce, K. C.; Stone, M. H. (Strength and Conditioning Journal, 2008)
The introduction of novel training stimuli plays a crucial role in inducing specific training adaptations. One method that can be employed to introduce a novel stimulus to the training program while maximising the velocity and power output of the training exercise is the inclusion of the cluster set of configuration. The current reviews presents the theoretical and research foundation for the use of the cluster set in periodized training programs and offers examples of practical applications that can be used in the preparation of athletes in a variety of sports.